Analisis Nilai Pendidikan Karakter dalam Novel Negeri 5 Menara Karya Ahmad Fuadi - Juliani, Syafira; Kartolo, Rahmat (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2023)
The novel "Negeri 5 Menara" is a fictional work that presents an imaginative world, portraying an idealized model of life through intrinsic elements such as events, plots, characters, settings, and points of view. The study aims to explore the values of character education depicted in the novel. Using a descriptive qualitative method, data is collected through reading and understanding the novel. Data analysis includes reading, describing, analyzing, identifying, and drawing conclusions. The novel serves as the primary source for this research. The findings reveal the presence of religious values, discipline, social care, and patience in the novel, providing readers with valuable insights into character education. These values offer a unique enthusiasm for education, making the novel a valuable resource for character development.